2021
DOI: 10.1039/d1ta03712a
|View full text |Cite
|
Sign up to set email alerts
|

Importance of small loops within PIM-1 topology on gas separation selectivity in thin film composite membranes

Abstract: Studies of blends of topologically distinct samples of the polymer of intrinsic microporosity PIM-1 provide, for the CO2/N2 gas pair, insight into the optimum loop topology required for high selectivity and permeance of thin film composite (TFC) membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…All films cast from polymer samples containing more than 10 wt % colloidal network material exhibited nontypical aging behavior between 1 and 143 days: both permeability and selectivity decreased upon aging. This negative aging behavior has been previously observed in thin film composite membranes cast from blends of PIM-1, which contained high amounts of colloidal network material, after a couple of months . The presence of a second colloidal network phase in the bulk presents at the very least a second mode of aging within the overall films.…”
Section: Resultssupporting
confidence: 71%
“…All films cast from polymer samples containing more than 10 wt % colloidal network material exhibited nontypical aging behavior between 1 and 143 days: both permeability and selectivity decreased upon aging. This negative aging behavior has been previously observed in thin film composite membranes cast from blends of PIM-1, which contained high amounts of colloidal network material, after a couple of months . The presence of a second colloidal network phase in the bulk presents at the very least a second mode of aging within the overall films.…”
Section: Resultssupporting
confidence: 71%
“…However, the pristine PIM-1 membranes in our previous work suffer a larger extent of physical aging than the ones used in this work over the same period (Table ); it is worth noting that two different PIM-1 batches were used, and the observed higher gas permeabilities for MMMs containing ODA-HGO-4h may be related to the polymer itself. Foster et al , found that the presence of branched PIM-1 chains (formed during the polymer synthesis as a consequence of incomplete disubstitutions) results in slower physical aging as compared to linear polymeric structures. NMR characterization (Figure S8) suggests the presence of branched polymer structures within the PIM-1 sample employed in this manuscript, which accounts for the slower physical aging as compared to the PIM-1 sample reported in our previous publication.…”
Section: Results and Discussionmentioning
confidence: 99%
“…41 More recently, Foster et al reported the effect of blending topologically distinct samples of PIM-1 on the performance and aging behaviour of TFCs. 42 Those containing a multi-loop polymeric structure (with 3 small loops) and very few chain ends (0–1 max) showed the best aging behaviour, with CO 2 permeance of 671 GPU after 120 days.…”
Section: Resultsmentioning
confidence: 96%
“…41 More recently, Foster et al reported the effect of blending topologically distinct samples of PIM-1 on the performance and aging behaviour of TFCs. 42 Those containing a multi-loop polymeric structure (with 3 small loops) and very few chain ends (0-1 max) showed the best aging behaviour, with CO 2 permeance of 671 GPU aer 120 days. Some of the prepared TFN membranes with aminefunctionalised-rHGO were able to reduce the physical aging of the PIM-1 polymer, for example the membrane containing 0.25 wt% of tetrakis (TFN-0.25rHGO-tetrakis) experienced a loss of CO 2 permeance of only 14% (from (1265 AE 70) to (1092 AE 108) GPU) over a period of 66 days.…”
Section: Resultsmentioning
confidence: 97%